Nucleic acid derived indices or instantaneous growth rate as tools to determine different nutricional condition in cuttlefish (Sepia officinalis, linnaeus 1758) hatchlings - Sykes, António V. (2018)
Two groups of 100 cuttlefish hatchlings each were used to determine the duration of the yolk reserves, during which growth can be obtained with no food supply. One group was fed live grass shrimp ad libitum from the 3rd day of life onwards, while the other was starved during the whole experiment. The experiment lasted 7 days, because this was the 1st day where a negative growth rate was obtained. Nucleic acid derived indices and instantaneous growth rates (IGR) were used as a way to describe their condition, when all the yolk reserves would be exhausted and to determine the most accurate tool to express growth and condition. RNA/DNA ratios described clearly the differences (P < 0.05) between fed and starved hatchlings cultured at 23 ± 2°C, especially from day 4 onwards. Correlation between IGR and RNA/DNA ratios was only attained for the starved population (R 0.90; P 0.0374). DNA concentration was identical (P > 0.05) between groups and did not displayed a clear pattern with increasing age. Correlation between IGR and DNA was only attained for the fed population (R −0.90; P 0.0374). RNA concentration values were different from day 5 onwards. Any of the nucleic acid derived indexes were not accurate enough to express growth and condition, so IGR seems to be the most accurate and inexpensive way to describe hatchlings growth and condition in controlled conditions.